Barriers to Success? The Role of Statewide Education Governance Structures in P-20 Council Collaboration - Jennifer Rippner (Arizona State University, 2015)
Collaboration between K-12 and higher education sectors has not been as productive as participants and policy leaders would like - especially in an era of emphasis on college readiness and completion, which requires such collaboration. Various mechanisms have been used to foster collaboration including state P-20 (early learning through higher education) councils, however these have not always produced the results participants desire and research on why this is so is limited. This study utilizes state education governance and inter-organizational relations literatures to hypothesize that structural barriers to collaboration prevent P-20 councils from reaching their potential. This comparative case study of three state P-20 councils finds that state education governance structures may erect barriers to collaboration. However, this research also shows that P-20 councils, if thoughtfully structured, can help ameliorate these barriers.